ANALYSIS ON COMPENSATION FOR LAND TENURE USE THE RIGHT USED IN LAND ACQUISITION FOR THE PUBLIC INTEREST (STUDY ON LAND ACQUISITION FOR PUBLIC INTEREST IN SINGKAWANG) - - A11112067, RAFIKHAN ADLAN (Jurnal Hukum Prodi Ilmu Hukum Fakultas Hukum Untan (Jurnal Mahasiswa S1 Fakultas Hukum) Universitas Tanjungpura, 2016)
Procurement of land has a direct connection with the use or utilization of land as the Government Regulation No. 16 of 2004 on Land Stewardship. The legal procedures for land acquisition must be accompanied by the release / delivery and holders of land rights to another party. The release itself can be selling, assignment grant or revocation. Special release that apply for land acquisition in the sense of surrender in exchange for compensation, or a waiver unilateral revocation of rights by the government. Revocation itself should be preceded by a consultation process at the time of land acquisition activities with compensation, but did not get a consensus on the amount of compensation, or the existing court decision which inkrah. Revocation right to land by the State against the rights of individuals or institutional, in fact the State is entitled as a realization of the rights of the State unmtuk master, process and manage all real estate related. Including plants and objects berakiban with soil. State's own in use rights associated with the land can not be arbitrary but no juridical conditions that must be obeyed by the State. Certainly based on the legislation in force. Soil is a natural resource that is not renewable, because the interest will be the soil is always cause various problems, one of them is the provision of land for public purposes, procurement of land for public use that occurred in Singkawang that public facilities are terminal, however there are two a different opinion in interpreting its ground state after over its useful Rights. Â Â Keywords: Land State, former right Wear And Indemnity